The in vivo treatment with the plant urease “Jack Bean Urease” impaired reproduction in females of Rhodnius prolixus (Hemiptera: Reduviidae) - Fruttero, Leonardo L. (2022)
Ureases are enzymes that catalyze the hydrolysis of urea to carbon dioxide and ammonia. In recent decades, it has been postulated that plant ureases are also defense proteins against phytophagous insect species with potential biotechnological application. Previous reports demonstrated that the injection of "Jack Bean Urease" (JBU), the major isoform of urease from the legume Canavalia ensiformis, into the hemocele of triatomine insects, resulted in several toxic effects including activation of the immune response. Although the insecticidal effect of JBU was described several years ago, many aspects of its mechanism of action as well as the target organs remains largely uncharacterized. In particular, the effects of JBU on the female reproductive system and the consequences of sublethal doses have not been studied.